Attitudes towards hearing difficulties, health-seeking behaviour, and hearing aid use among older adults in Thailand - Pornprasit, Panicha; Utoomprurkporn, Nattawan; Areekit, Poonsub; Manum, Pornnapat; Thanutammakul, Sutatta; Parmar, Bhavisha; Adamson, Joy; Bamiou, Doris (Frontiers in Digital Health, 2024)
This study explores older adults' attitudes toward hearing difficulties, health-seeking behaviour and hearing aids use in Thailand. Three focus groups (n=25) were conducted within a residential complex for older adults in Samutprakarn, Thailand.Qualitative data analysis, employing a phenomenological approach was completed and four overarching themes are presented: (1) Perception of hearing difficulties, (2) Experience of receiving care, (3) Attitudes towards wearing hearing aids, and (4) Raising awareness of hearing difficulties in older adults. Findings indicated that Thai older adults may not be aware or accepting of their hearing difficulties, due to the stigma associated hearing loss, older age, and disability. The consequential impact of these unacknowledged issues manifests in communication challenges and the adoption of avoidance behaviors across diverse situational contexts. Findings also underscore the potential pivotal role of familial and social networks in mitigating barriers associated with hearing difficulties among older adults in Thailand.This study enhances our understanding of how Thai older adults perceive hearing problems and ear care. These insights can raise awareness and inform effective management for older adults and their families. Additionally, the findings could guide healthcare providers, researchers, and policy makers, fostering improved care for this demographic.